Status of planktonic copepod diversity in the Merambong seagrass meadow, Johor, Peninsular Malaysia - Peralta, Hazel Monica Matias; Md. Yusoff, Fatimah (Scientific & Academic Publishing, 2015)
The diversity and abundance of planktonic copepods were analysed from zooplankton samples collected within six times throughout the year in the Merambong seagrass area. A total of 48 species from 20 genera and 15 families comprising an average of 78.8%, of the total zooplankton populations were recorded throughout the sampling period. Among the copepod groups, calanoids were the most abundant inhabiting all the stations, taking an average of 51.2% of the total copepod populations. The most common species observed in the area were Paracalanus parvus, Paracalanus elegans, Oithona rigida, and Euterpina acutifrons. The highest copepod density was recorded at 17.0±2.8 x104 individuals/m3. Copepod species diversity (H’) and species richness (d) were highest at H’ = 3.58 and d=7.08, respectively. Species evenness (J) was, however, relatively constant (0.9) during the entire sampling period. The findings from this study provide important baseline information for future research and monitoring programs.